Engineering principles for guiding spheroid function in the regeneration of bone, cartilage, and skin. (21st March 2018) - Gionet-Gonzales, Marissa A; Leach, J Kent
Abstract: There is a critical need for strategies that effectively enhance cell viability and post-implantation performance in order to advance cell-based therapies. Spheroids, which are dense cellular aggregates, overcome many current limitations with transplanting individual cells. Compared to individual cells, the aggregation of cells into spheroids results in increased cell viability, together with enhanced proangiogenic, anti-inflammatory, and tissue-forming potential. Furthermore, the transplantation of cells using engineered materials enables localized delivery to the target site while providing an opportunity to guide cell fate in situ, resulting in improved therapeutic outcomes compared to systemic or localized injection. Despite promising early results achieved by freely injecting spheroids into damaged tissues, growing evidence demonstrates the advantages of entrapping spheroids within a biomaterial prior to implantation. This review will highlight the basic characteristics and qualities of spheroids, describe the underlying principles for how biomaterials influence spheroid behavior, with an emphasis on hydrogels, and provide examples of synergistic approaches using spheroids and biomaterials for tissue engineering applications.